Bibliometric Map of Educational Robotics Studies - Akgun, Muhterem; Atici, Bunyamin (Int Soc Technology Education & Science-Istes, 2023)
The purpose of this study is to determine the general trend of research in the field of educational robotics through bibliometric analysis. 1382 papers indexed in the WOS database between 1975-2021 were subjected to bibliometric analyses. The data of the study were analyzed using VOSviwer and SciMAT. At the end of the study, it has been concluded that in the field of educational robotics the most productive country was the USA, the most influential journal was Computers and Education, the most influential author was Bers, M.U., and the most influential institution was Tufts University. It has been also concluded that computational thinking, STEM, coding, programming, social robots, and communication themes have become a trend in the field of educational robotics in recent years.
Keywords: Educational robotics; Bibliometric analysis; STEM; Computational thinking; Programming